Numerical Analysis of Angular Dissimilarity of Static Loads in Honeycomb Structures Substantial Flexural Strength - Siahaan, M. Yusuf Rahmansyah; Siregar, Rakhmad Arief; Siregar, Amru; Nasution, Ahmad Yunus (Suara Teknik : Jurnal Ilmiah, 2023)
Three-dimensional (3D) imaging technology for computer-assisted construction planning of a product through a simulation process is now having a very positive impact in helping to improve the construction results of a product. The honeycomb shape has better strength in accepting constant and stable loads and has a lighter structure. Aluminum honeycomb using the sandwich construction method was analyzed by simulation using Ansys software in this research based on 3 variations in hexagonal cell geometry due to differences in the applied static load. The influence of the hexagonal honeycomb cell geometry shows a contribution to the deformation capability of the material at varying load angles, namely an increase of 100% at a load angle of 60° and a higher spike of around 130% for a load angle of 90°. Variations in the hexagonal honeycomb geometry still have an impact on increasing material capability. of 128% in the 6 mm hexagonal cell model with a load angle of 90°. The geometric intensity of the honeycomb hexagonal cell produces expansion values respectively in material deformation and equivalent stress based on the load angle of 15% and 35%.